2006
DOI: 10.1017/s0033291706008397
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual abuse and risks for licit and illicit drug-related outcomes: a twin study

Abstract: Background. This study examined the relationships between self-reported childhood sexual abuse (CSA) and drug-related outcomes in an Australian twin panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
102
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 48 publications
11
102
0
2
Order By: Relevance
“…Consistent with prior studies of trauma exposure and PTSD, elevated rates of parental problem drinking (Dube et al, 2001;Fergusson et al, 1996b;Sher et al, 1997), MDD (Breslau et al, 1997;Hapke et al, 2006;Kendler et al, 2000;McCutcheon et al, 2009), CD (Afi fi et al, 2009Fu et al, 2007;Kessler et al, 1995;Koenen et al, 2002), regular smoking (Al-Mamun et al, 2007;Breslau et al, 2003;Nelson et al, 2006), and cannabis abuse (Duncan et al, 2008;Kilpatrick et al, 2000;Nelson et al, 2006;Reed et al, 2007) were observed in women who had experienced traumatic events-both those who developed PTSD and those who did not-compared with women who did not report any trauma exposure. Much of the prior research in this area has involved comparing rates of co-occurring psychopathology and psychosocial risk factors in individuals with PTSD with those who do not meet diagnostic criteria, without regard to the trauma exposure status of individuals in the non-PTSD group or, conversely, comparing traumaexposed with non-trauma-exposed individuals, without regard to the PTSD status of individuals in the traumaexposed group.…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 76%
See 1 more Smart Citation
“…Consistent with prior studies of trauma exposure and PTSD, elevated rates of parental problem drinking (Dube et al, 2001;Fergusson et al, 1996b;Sher et al, 1997), MDD (Breslau et al, 1997;Hapke et al, 2006;Kendler et al, 2000;McCutcheon et al, 2009), CD (Afi fi et al, 2009Fu et al, 2007;Kessler et al, 1995;Koenen et al, 2002), regular smoking (Al-Mamun et al, 2007;Breslau et al, 2003;Nelson et al, 2006), and cannabis abuse (Duncan et al, 2008;Kilpatrick et al, 2000;Nelson et al, 2006;Reed et al, 2007) were observed in women who had experienced traumatic events-both those who developed PTSD and those who did not-compared with women who did not report any trauma exposure. Much of the prior research in this area has involved comparing rates of co-occurring psychopathology and psychosocial risk factors in individuals with PTSD with those who do not meet diagnostic criteria, without regard to the trauma exposure status of individuals in the non-PTSD group or, conversely, comparing traumaexposed with non-trauma-exposed individuals, without regard to the PTSD status of individuals in the traumaexposed group.…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 76%
“…Rates of MDD (Dinwiddie et al, 2000;Kendler et al, 2000;McCutcheon et al, 2009;Nelson et al, 2002), CD (Afi fi et al, 2009;Fergusson et al, 1996a;Molnar et al, 2001), cannabis and other illicit drug use disorders (Duncan et al, 2008;Kendler et al, 2000;Kilpatrick et al, 2000) and smoking (Al-Mamun et al, 2007;Anda et al, 1999;Nelson et al, 2006) are elevated in trauma-exposed populations. Thus, in examining the relationship between PTSD and alcohol-related outcomes, it is critical to adjust for the potential confounding effects of these commonly co-occurring conditions on the association of both PTSD and trauma exposure with AUDs.…”
mentioning
confidence: 99%
“…Consistent with an extensive literature linking CSA to early and problem use of marijuana (Bensley et al, 1999;Harrison et al, 1997;Kilpatrick et al, 2000;Nelson et al, 2006), the likelihood of ever using marijuana, using marijuana at a young age, and developing CUD symptoms was elevated in both AA and EA women with a history of CSA. Regression analyses incorporating sibling status on marijuana outcomes revealed that the contribution of CSA to risk for use and development of CUD symptoms in both racial/ethnic groups was independent of familial risk factors common to exposure to CSA and early (or problem) marijuana use.…”
Section: Childhood Sexual Abuse and Marijuana Outcomes In African-amesupporting
confidence: 75%
“…CSA is also associated with early initiation of marijuana use (Bensley et al, 1999;Harrison et al, 1997;Kilpatrick et al, 2000;Nelson et al, 2006), a marker of risk for the development of cannabis use disorder (CUD; Anthony & Petronis, 1995;King & Chassin, 2007). Early use itself is a health concern as well because it typically means longer than average exposure to marijuana and-even more importantly-exposure during a crucial period of brain development, with the potential for long-term impact on cognitive functioning (Ashtari et al, 2011;Bava & Tapert, 2010) as well as other psychopathology (Volkow et al, 2014).…”
Section: N Estimated One In Five Women In the Unitedmentioning
confidence: 99%
“…N UMEROUS STUDIES HAVE SUGGESTED that childhood adversity and stress, including abuse and neglect, may lead to problems with substance use (e.g., Bensley et al, 1999;Fergusson et al, 2008;Nelson et al, 2006;Simpson and Miller, 2002;Wand, 2000;Widom et al, 2006). However, most research on this relationship has used crosssectional designs relying on retrospective reports of child abuse and neglect, often from adults identifi ed as substance users.…”
mentioning
confidence: 99%